(untitled) (Studia austriaca, 2017)
This article offers an inventory of the rarely analyzed poetry of the mythical Austrian Empress and thereby shows the masterful self-presentation of a historically ambivalent personality. Using selected poems, this article brings out Elizabeth’s appraisal of the contemporary court society, for which she often had only biting scorn. Her poetry reveals an almost religious veneration for Heinrich Heine and an almost subversive attitude towards the k.u.k. monarchy. It also illustrates Elizabeth’s literary strategy of dismantling a hated society, though its effect could also be interpreted to the contrary, i.e. as an unintended contribution of the opposition to the transfiguration of the Habsburg myth.